Byzantine Kastra in the Dark Ages: the case of Oria Kastro on Kythnos - Veloudaki, Christianna (Journal of Greek Archaeology, 2019)
During the first three centuries after the founding of the Eastern Empire, the islands of the Cyclades in the Aegean Sea knew a period of relative calm and prosperity, acting as supply stations for vessels following the sea routes to and from Constantinople. Most of them had flourishing maritime market towns that functioned as processing and exporting centres. From the 7th century onwards, however, it can be observed that many of these ancient coastal cities either shrank dramatically in size or were gradually abandoned and the so-called kastra, i.e. fortified settlements built on top of remote hilltops, took their place. Little is known about this transitional period (7th-9th century AD) in the Aegean world as there are barely any written sources and most of the ancient cities and the Byzantine kastra in the Cyclades remain undocumented. Consequently, the beginning of the transition process and the exact causes behind it remain unclear. Pirate raids and the Arab threat after the 640s are the reasons traditionally put forward by Greek and foreign scholars, however, recent studies suggest that the Arab fleets are unlikely to have been a serious threat to the islands before the occupation of Crete by the Andalus Muslims in AD 827.